Evaluate $\displaystyle \lim_{x \to 1} \dfrac{\sin(x-1)}{x^2 -1}$

The angle of a right angled triangle is expressed as $x-1$. The value of the ratio of $\sin(x-1)$ to $x^2 -1$ is required to find when the value of limit $x$ tends to $1$.

Step: 1

Substitute $x = 1$ to test this function.

$\Large \displaystyle \lim_{x \to 1} \normalsize \dfrac{\sin(x-1)}{x^2 -1}$ $=$ $\dfrac{\sin(1-1)}{{(1)}^2 -1}$

$\implies \Large \displaystyle \lim_{x \to 1} \normalsize \dfrac{\sin(x-1)}{x^2 -1}$ $=$ $\dfrac{\sin (0)}{1-1}$

$\implies \Large \displaystyle \lim_{x \to 1} \normalsize \dfrac{\sin(x-1)}{x^2 -1}$ $=$ $\dfrac{0}{0}$

We have obtained an indeterminate form in substitution method when the value of $x$ is replaced by $1$. So, it has to be solved in another way.

In numerator, the angle is $x-1$ and it can be obtained in denominator as well by expressing $x^2 -1$ as two multiplying factors in which $x-1$ is one of them.

$\implies \Large \displaystyle \lim_{x \to 1} \normalsize \dfrac{\sin(x-1)}{x^2 -1}$ $=$ $\Large \displaystyle \lim_{x \to 1} \normalsize \dfrac{\sin(x-1)}{(x-1)(x+1)}$

Step: 2

Split the ratio of the functions as two multiplying factors.

$= \Large \displaystyle \lim_{x \to 1} \normalsize \Bigg[ \dfrac{\sin(x-1)}{(x-1)} \times \dfrac{1}{(x+1)} \Bigg]$

$= \Large \displaystyle \lim_{x \to 1} \normalsize \Bigg[ \dfrac{\sin(x-1)}{(x-1)}\Bigg] \times \Bigg[\dfrac{1}{(x+1)} \Bigg]$

Step: 3

Apply the limit to both multiplying functions by the product rule.

$= \Large \displaystyle \lim_{x \to 1} \normalsize \Bigg[ \dfrac{\sin(x-1)}{(x-1)} \Bigg]$ $\times$ $\Large \displaystyle \lim_{x \to 1} \normalsize \Bigg[\dfrac{1}{(x+1)} \Bigg]$

Step: 4

The first multiplying factor represents the relation of sine of angle with angle and it is same the limit x tends to 0 sinx/x rule. According to this identity, the quotient of sine of angle by angle is one when $x$ approaches zero. So, let us try to adjust the first multiplying factor.

If $x$ tends to $1$, then $x-1$ tends to $0$. So, change the limit value $x \to 1$ to $x-1 \to 0$ but only for the first multiplying function.

$= \Large \displaystyle \lim_{x-1 \to 0} \normalsize \Bigg[ \dfrac{\sin(x-1)}{(x-1)} \Bigg]$ $\times$ $\Large \displaystyle \lim_{x \to 1} \normalsize \Bigg[\dfrac{1}{(x+1)} \Bigg]$

Therefore, the value of first multiplying factor is $1$ and substitute $x=1$ in the second multiplying factor to obtain the required solution.

$= 1 \times \dfrac{1}{1+1}$

$= 1 \times \dfrac{1}{2}$

$\therefore \,\,\,\,\,\, \displaystyle \Large \lim_{x \to 1} \normalsize \dfrac{\sin(x-1)}{x^2 -1} = \dfrac{1}{2}$

Latest Math Topics
Latest Math Problems

A best free mathematics education website for students, teachers and researchers.

Maths Topics

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

Maths Problems

Learn how to solve the maths problems in different methods with understandable steps.

Learn solutions

Subscribe us

You can get the latest updates from us by following to our official page of Math Doubts in one of your favourite social media sites.